2013
DOI: 10.1371/journal.pone.0058704
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Tree Species Governs the Spatio-Temporal Interaction of Leaf Area Index and Soil Moisture across a Forested Landscape

Abstract: Quantifying coupled spatio-temporal dynamics of phenology and hydrology and understanding underlying processes is a fundamental challenge in ecohydrology. While variation in phenology and factors influencing it have attracted the attention of ecologists for a long time, the influence of biodiversity on coupled dynamics of phenology and hydrology across a landscape is largely untested. We measured leaf area index (L) and volumetric soil water content (θ) on a co-located spatial grid to characterize forest pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…Similarly, Naithani et al (2013) found that soil moisture and vegetation patterns are very similar from leaf-onset to maturity but different from leaf maturity to senescence. Overall, the factors influencing soil moisture are related to the presence or absence of vegetation (Gómez-Plaza et al, 2001).…”
mentioning
confidence: 86%
“…Similarly, Naithani et al (2013) found that soil moisture and vegetation patterns are very similar from leaf-onset to maturity but different from leaf maturity to senescence. Overall, the factors influencing soil moisture are related to the presence or absence of vegetation (Gómez-Plaza et al, 2001).…”
mentioning
confidence: 86%
“…The leaf surface is the site of water vapor exchange, and therefore, leaf area, which can be reflected by LAI, controls tree transpiration (Kikuzawa, 1995;Naithani et al, 2013;Sellers et al, 1997). We did not perform an in situ measurement of LAI; a Moderate Resolution Imaging Spectroradiometer (MODIS) LAI product (MCD15A3) was adopted as the observation value.…”
Section: Leaf Area Index Observationsmentioning
confidence: 99%
“…1). The catchment is largely vegetated by deciduous trees (maple, oak, and beech) as well as hemlock and pine (Lin, 2006;Naithani et al, 2013). The catchment experienced two significant perturbations in the geologically recent past: a perturbation from peri-glacial to modern conditions ($15 kyr; Gardner et al, 1991) that has affected long-term regolith formation processes (Ma et al, 2010, and clearing of forests during colonial occupation that represents a short-term disturbance to local ecology and the environment.…”
Section: Study Areamentioning
confidence: 99%